2022
DOI: 10.1186/s13065-022-00850-w
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous spectrophotometric determination of finasteride and tadalafil in recently FDA approved Entadfi™ capsules

Abstract: Entadfi™ is a recently FDA approved pharmaceutical combination capsule of finasteride and tadalafil. It was prescribed for the treatment of urinary tract disorders caused by benign prostatic hyperplasia in men. This paper introduced the first spectrophotometric methods for simultaneous determination of finasteride and tadalafil in the pure form and in the pharmaceutical capsules. UV absorption spectra of finasteride and tadalafil exhibited overlap hindered the direct simultaneous determination of the cited dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As shown in Table 3 , the results of the proposed methods were statistically compared with that of the reported one. 17 The values of t and F tests do not surpass the theoretical values, thus advocating that there is no significant variation between the developed methods in the proposed study and the reported one.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…As shown in Table 3 , the results of the proposed methods were statistically compared with that of the reported one. 17 The values of t and F tests do not surpass the theoretical values, thus advocating that there is no significant variation between the developed methods in the proposed study and the reported one.…”
Section: Resultsmentioning
confidence: 61%
“…Table 5 shows a comprehensive greenness behavior difference between the proposed methods and that of the reported one 17 for the quantification of FIN and TAD. Regarding the eco-scale applied tool, the eco-scale scores of the three methods were above 75, revealing the excellent green analytical method of analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational chemistry represents an integral approach, in HPLC [4] , [5] , spectrophotometry [6] , [7] and electrochemistry [8] , to the development of greener methods based on theoretical testing of compound interactions and reducing the use of toxic solvents [9] . Many analytical methods have been developed to demonstrate the quality of the drug materials including HPLC [10] , TLC [11] , specroflorimetry [12] , [13] , [14] , [15] , [16] , [17] as well as spectrophotometry [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Thin layer chromatographic method and high-pressure liquid chromatographic methods were reported for the determination of TAD and CAN [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Spectrofluorimetric and spectrophotometric methods were reported for the determination of both drugs [24][25][26][27][28][29][30][31][32]. Quantitation of TAD by gas chromatography was reported [33,34].…”
Section: Introductionmentioning
confidence: 99%